2013
DOI: 10.1007/s11999-013-2803-3
|View full text |Cite
|
Sign up to set email alerts
|

Total Knee Arthroplasty in the Elderly: Does Age Affect Pain, Function or Complications?

Abstract: Background TKA is one of the most commonly performed procedures in the elderly, yet whether age influences postoperative pain, function, and complication rates is not fully understood for this group. This is because the current literature has limited followup, small sample sizes, and no comparator group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
87
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(96 citation statements)
references
References 22 publications
5
87
2
1
Order By: Relevance
“…Consistent with the results of other studies, the older group of patients (> 65 years) was likely to stay in the hospital longer than the younger group (≤65 years) [7,[18][19][20]. Older patients tend to be in worse physical condition and more likely to have postoperative complications [21,22], which increases the LOS. Furthermore, older patients are more likely to live alone and need caregiver support than are younger patients, and these factors have been shown to be important predictive factors for an extended LOS [6].…”
Section: Discussionsupporting
confidence: 85%
“…Consistent with the results of other studies, the older group of patients (> 65 years) was likely to stay in the hospital longer than the younger group (≤65 years) [7,[18][19][20]. Older patients tend to be in worse physical condition and more likely to have postoperative complications [21,22], which increases the LOS. Furthermore, older patients are more likely to live alone and need caregiver support than are younger patients, and these factors have been shown to be important predictive factors for an extended LOS [6].…”
Section: Discussionsupporting
confidence: 85%
“…Meehan et al [20] showed that patients younger than 50 years are more likely to undergo revision as a result of PJI or aseptic mechanical failure at 1 year after TKA. Similarly, the higher rates of AKA in older populations could be the result of differences in comorbidities and/or patient preferences [13]. The higher rates in older patients could also be the result of the methodology used in this study.…”
Section: Discussionmentioning
confidence: 93%
“…First, our finding that Medicare payments were higher for several patient populations (women, older patients, and patients with greater comorbid illness) is not unexpected; our findings are likely a reflection of both higher complication rates for TKA in these subgroups and less social support necessitating greater reliance on home health services. [23][24][25][26] The implications of higher complication rates (and costs) for certain populations could have profound implications under a switch to bundled payments. To the extent that patients with similar sociodemographics (and risk for complications) cluster within hospitals, [27][28][29] certain hospitals could benefit by having a relatively low-risk TKA population and see profits from TKA soar; alternatively, other hospitals with a predominantly higher risk TKA population could see TKA as financially detrimental based upon geographic location and catchment area alone.…”
Section: Discussionmentioning
confidence: 99%